Exploring parkrun as a social context for collective health practices: running with and against the moral imperatives of health responsibilisation. Issue 1 (8th October 2017) - Wiltshire, G. R.; Fullagar, Simone; Stevinson, Clare
Abstract: Critiques of public health policies to reduce physical inactivity have led to calls for practice‐led research and the need to reduce the individualising effects of health promotion discourse. The purpose of this paper is to examine how parkrun – an increasingly popular, regular, community‐based 5 km running event – comes to be understood as a 'health practice' that allows individuals to enact contemporary desires for better health in a collective social context. Taking a reflexive analytical approach, we use interview data from a geographically diverse sample of previously inactive parkrun participants (N = 19) to explore two themes. First, we argue that parkrun offers a space for 'collective bodywork' whereby participants simultaneously enact personal body projects while they also experience a sense of being 'all in this together' which works to ameliorate certain individualising effects of health responsibilisation. Second, we examine how parkrun figures as a health practice that makes available the subject position of the 'parkrunner'. In doing so, parkrun enables newly active participants to negotiate discourses of embodied risk to reconcile the otherwise paradoxical experience of being an 'unfit‐runner'. Findings contribute to sociological understandings of health and illness through new insights into the relation between health practices and emerging physical cultures, such as parkrun .